Kajian Pengelolaan Keuangan Daerah Kabupaten Jayapura Pada Era Otonomi Khusus - Hutajulu, Halomoan; Sanggrangbano, Agustina; Bonay, Antonia K. (Jurnal Ekonomi Kuantitatif Terapan, 2012)
Ineffectiveness of regional financial management will certainly lead to the implementation of regional development are not optimal. Depart from the concept in mind, it is interesting to examine and analyze the issue of how to measure the effectiveness of financial management in the Jayapura District on the Special Autonomy Era. The analysis result showed that generally, area of financial management in Jayapura District running less effective. Other than that the amount of contributions of the fund balance at the regional income shows high dependency of revenue sharing. The expenditure side tends to minimize the increase in regular budget expenditure for development (public), hence the macro does not much affect the acceleration of economic development. The budget deficit system will optimize development in three ways. First, the government's efforts to optimize the internal resources possessed to reduce dependency on fund balance by mapping and restructuring local revenue. Second, the government must set clear priorities of regional development budget allocation according to the concept of value for money. Third, the budget deficit or surplus principle for the government is an innovative way for any action to encourage productive economic activity.
Keywords: effectiveness; regional finance; Jayapura Districs; special autonomy